Retrospective Study of B Lymphoblastic Leukemia to Assess the Prevalence of TEL/AML1 in South India: A Study of 214 Cases and Review of Literature - Sandhya Devi G.; Faiq Ahmed; Manasi C. Mundada; Rachna Khera; Lavanya Nambaru; Krishnamohan Mallavarapu; Pavan Kumar Boyella; Veerandra Patil; Pallavi Suresh Laddha; Senthil J. Rajappa (Indian Journal of Medical and Paediatric Oncology)
Introduction Translocation t(12;21)(p13;q22), a recurrent and an invisible chromosomal abnormality, resulting in TEL/AML1 gene fusion, associated with good prognosis, has been described to be a common abnormality, in children with B-acute lymphoblastic leukemia (B-ALL).